Do High Potential Employees Always Possess Emotional Intelligence? A Narrative Review of the Competency Based Model in Indonesian Multisector Organizations (2024–2025) - Anang Setiawan (Economics and Business Journal (ECBIS), 2026)
This narrative review explores whether high-potential workers (HiPo) within Indonesian organizations across various sectors consistently exhibit elevated levels of emotional intelligence (EI), and it assesses the relevance of the Competency Based Model proposed by Boyatzis in the identification and development of HiPos. The review compiles freely accessible scholarly articles from 2024 to 2025, with a focus on research from Indonesia and includes one primary benchmark study on high-potential individuals for comparison, as studies specific to Indonesian HiPo are scarce. Findings reveal that being classified as a HiPo does not necessarily correlate with having high EI. Research directly related to high potential employees indicates that cognitive-intrapersonal skills such as initiative, desire for learning, and the ability to think outside conventional limits are stronger indicators of high potential than emotional-interpersonal skills. Research from various Indonesian sectors, including manufacturing, energy, construction, and public services, suggests that while EI plays a significant role in enhancing employee productivity, work performance, job satisfaction, and effectiveness in management, its influence typically operates through mediating factors instead of serving as a direct predictor. Furthermore, talent management research in Indonesia shows that numerous organizations still depend on performance evaluations and fragmented methods instead of comprehensive competency frameworks. This review concludes that the Competency Based Model is relevant in Indonesian organizations across different sectors; however, it should be viewed as encompassing a range of competencies rather than a single attribute. While EI is valuable, it is not an essential or sufficient criterion for determining high-potential employees.